The East Asian challenge for democracy : political meritocracy in comparative perspective - Bell, Daniel (Daniel A.), 1964- (Cambridge : Cambridge University Press, 2013)
The rise of China, along with problems of governance in democratic countries, has reinvigorated the theory of political meritocracy. But what is the theory of political meritocracy and how can it set standards for evaluating political progress (and regress)? To help answer these questions, this volume gathers a series of commissioned research papers from an interdisciplinary group of leading philosophers, historians and social scientists. The result is the first book in decades to examine the rise (or revival) of political meritocracy and what it will mean for political developments in China and the rest of the world. Despite its limitations, meritocracy has contributed much to human flourishing in East Asia and beyond and will continue to do so in the future. This book is essential reading for those who wish to further the debate and perhaps even help to implement desirable forms of political change.
Introduction: the theory, history, and practice of political meritocracy / Daniel A. Bell -- Political meritocracy and meritorious rule: A Confucian perspective / Joseph Chan -- A Confucian version of hybrid regime: how does it work, and why is it superior? / Tongdong Bai -- Confucian meritocracy for contemporary China / Ruiping Fan -- The liberal critique of democracy / John Skorupski -- Meritocratic representation / Philip Pettit -- Between merit and pedigree: evolution of the concept of'Elevating The Worthy' in Pre-imperial China / Yuri Pines -- A society in motion: unexpected consequences of political meritocracy in late imperial China, 1400-1900 / Benjamin Elman -- Meritocratic democracy: learning from the American Constitution / Stephen Macedo -- How East Asians view meritocracy: a Confucian perspective / Doh Chull Shin -- Political meritocracy in Singapore: lessons from the PAP government / Benjamin Wong -- Meritocracy and political liberalization in Singapore / Kenneth Paul Tan -- China's meritocratic examinations and the ideal of virtuous talents / Hong Xiao and Chenyang Li -- Reflections on political meritocracy: Its manipulation and transformation / Philippe C. Schmitter -- Political meritocracy and direct democracy: A hybrid experiment in California / Nicolas Berggruen and Nathan Gardels.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Democracy -- East Asia; East Asia -- Politics and government